"[T]Hat Where One Was, There Was The Other": Dreams of Queer Stories in Aphra Behn's The History of the Nun, or, the Fair Vow-Breaker (1689). Issue 2 (3rd April 2021) - Saxton, Kirsten T.
ABSTRACT: Throughout The History of the Nun's hetero-romance plot, Behn creates serial queer doublings which work structurally with other formal effects to queer gender itself, revealing the limits of hetero- cisgendered categories. The novel uses the formal conventions of space and time and the themes of writing/telling/reading to gesture toward the capacious possibilities of gender and to lay bare the limits, not only of binary notions of gender, but also of limiting social structures, including narration itself.